Burtons Legal Thesaurus 5th Edition: Over 10,000 Synonyms, Terms, and Expressions Specifically Related to the Legal Profession - Burton, William C. (New York : McGraw-Hill, 2013)
"The fifth edition of the classic, go-to reference for everyone in the profession of law . Updated with 1,000 essential new terms--from "Super PAC" to "same sex marriage"The first book of its kind when it was first published in 1980, Burton's has become a staple among lawyers, judges, paralegals, law students, and anyone else in law. Now, this fifth edition celebrates 35 years of this one-of-a-kind law reference tool, a field where the precision and accuracy of language is vital.William C. Burton, Esq. is a partner in the international law firm of D'Amato & Lynch and a former NY State Assistant Attorney General and Assistant Special Prosecutor"--
Keywords: Law -- Terminology -- United States; English language -- Synonyms and antonyms; BUSINESS & ECONOMICS / Reference